Cellular Reference Materials for DNA Damage Using Electrochemical Oxidation. (30th January 2020) - Atha, Donald H.; Cole, Omobola; Clancy, Breece; Tona, Alessandro; Reipa, Vytas
Abstract : Reference materials are needed to quantify the level of DNA damage in cells, to assess sources of measurement variability and to compare results from different laboratories. The comet assay (single cell gel electrophoresis) is a widely used method to determine DNA damage in the form of strand breaks. Here we examine the use of electrochemical oxidation to produce DNA damage in cultured mammalian cells and quantify its percentage using the comet assay. Chinese hamster ovary (CHO) cells were grown on an indium tin oxide electrode surface and exposed 12 h to electrochemical potentials ranging from 0.5 V to 1.5 V (vs Ag/AgCl). The resulting cells were harvested and analyzed by comet and a cell viability assay. We observed a linear increase in the percentage (DNA in tail) of strand breaks along with a loss of cell viability with increasing oxidation potential value. The results indicate that electrochemically induced DNA damage can be produced in mammalian cells under well-controlled conditions and could be considered in making a cellular reference material for the comet assay.